Estudio de prefactibilidad para la instalación de una planta productora de huevos orgánicos a partir de gallinas ponedoras - Montero Reyes, Vanessa (2023)
The chicken egg is one of the most consumed foods in the world today due to its great nutritional value and easy acquisition for the majority of the population. Currently, there is a marked trend towards the consumption of organic products and also maintain healthy lifestyles and respect the environment. The objective of this work is to demonstrate the technical, social, economic, financial and market viability for the installation of a plant that produces organic eggs from laying hens raised outdoors, in order to satisfy the needs explained above. The target market of the project are people from sectors A and B of Metropolitan Lima who seek to maintain a healthy lifestyle, respecting and caring for the environment, and who normally want to buy differentiated products, valuing the quality-price ratio. That’s why the demand for the project of 495 204 boxes of eggs x 12 units / year. The location of the plant was determined based on a study of macro and micro location, considering key evaluation factors for the project. The selected place was the district of Huaral in the province of Huaral. Regarding the optimal plant size for the project, after evaluating the market, productive resources, technology and the break-even point, the result obtained was the size of the market. Finally, the feasibility of the project is demonstrated as a result of the economic and financial analysis. A financial NPV of S/717 074, an IRR of 27,8 %, and a recovery period of 3,38 years were obtained.